PENGARUH TEMAN SEBAYA, CITRA TUBUH, DAN RISIKO GANGGUAN MAKAN DENGAN STATUS GIZI PELAJAR PUTRI DI KECAMATAN SUSUT, BANGLI - Iswari, Ni Kadek Aprilia Putri; Adhi, Kadek Tresna (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025DO - 10.24843/ACH.2025.v12.i01.p08, 2025)
ABSTRACT Peer influence to adolescents is greater than family, including the formation of a negative body image that encourages eating disorders in adolescents. These eating disorders have an impact on the quality of nutrient intake seen from food diversity which can affect the nutritional status of adolescent girls. The purpose of this study was to determine the relationship between peer influence, family characteristics, body image, risk of eating disorders, and food diversity with the nutritional status of female students. This study is an analytic observational study with a cross sectional design. The sample of this study were female students in SMA and SMK in Susut Sub-District, Bangli Regency, totaling 127 people. Data analysis was done univariable with descriptive analysis and bivariable with chi square test.  There was an association between peer influence (p=0.039), family characteristics including mother's occupation (p=0.007), body image (p=0.015), risk of eating disorders (p=0.004) with the nutritional status of female students. There is no relationship between family characteristics including father's education (p=0.675), mother's education (p=0.698), family income (p=0.909), food diversity (p=1.000) with BMI/U of female students. There is a relationship between peer influence, mother's occupation, body image, and risk of eating disorders with nutritional status of female students in Susut District, Bangli. Nutrition intervention policies for female students need to involve the active role of peers and it is hoped that adolescents can create a healthy environment for their peers in an effort to improve nutritional status and prevent nutritional problems in adolescents . Keywords:  Peers, Body Image, Eating Disorders, Adolescents